2016
DOI: 10.1016/j.jelechem.2016.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Silver ion deposition on gold and silver disc electrodes from aqueous solutions and from dry or wet [EMIM][NTf2] room-temperature ionic liquid

Abstract: Silver ion deposition on gold and silver disc electrodes from aqueous solutions and from dry or wet [EMIM][NTf 2 ] room-temperature ionic liquid

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The Ag + reduction occurs around 0.62 V SHE , while oxidation occurs at 0.54 V SHE , indicating a highly reversible deposition process. 70 Initially, all Pd baths show a large nucleation overpotential, and the anodic scans of the Pd 2+ solutions are similar to those of the Pd substrate. The reduction peak of Pd 2+ and Pd(II) oxide for all Pd baths are around 0.65 V SHE , while the reduction peak around 0.12 V SHE could be attributed to the reduction of adsorbed Pd(OH) x particles (or β -oxide) 68 originated from solution instability.…”
Section: Methodsmentioning
confidence: 90%
“…The Ag + reduction occurs around 0.62 V SHE , while oxidation occurs at 0.54 V SHE , indicating a highly reversible deposition process. 70 Initially, all Pd baths show a large nucleation overpotential, and the anodic scans of the Pd 2+ solutions are similar to those of the Pd substrate. The reduction peak of Pd 2+ and Pd(II) oxide for all Pd baths are around 0.65 V SHE , while the reduction peak around 0.12 V SHE could be attributed to the reduction of adsorbed Pd(OH) x particles (or β -oxide) 68 originated from solution instability.…”
Section: Methodsmentioning
confidence: 90%
“…The overvoltage at the zerocrossing, η 0 = −0.05 , of backward curves was close to its theoretical value predicted for reversible systems. 39,40 The CVs, overall, indicated an electrochemical behaviour largely influenced by the nature of the working electrode. However, a linear relationship between the cathodic peak current density and the square root of the scan rate � = � 1 2 ⁄ ��, in Mo and Cu electrodes, indicated that the reduction of Sn 2+ were governed by diffusion-controlled processes 8,41,42 ( Figure S2) as follows :…”
Section: Resultsmentioning
confidence: 99%
“…STM-based studies of Ag single-crystal facets revealed the dynamics of underpotential deposition (UPD), overpotential deposition (OPD), as well as multilayer growth, which has provided a basis for models of nucleation and growth. 28–31 Liu et al measured Ag + ion deposition onto Ag-disk electrodes, and found slower kinetics than others found in water, although because of complications associated both with the uncertain microscopic structure of the electrodes studied, and the many underlying assumptions implicit in the analytical models used to analyze the resulting voltammograms, 32 we are hesitant to directly compare to the kinetic parameters here (ESI, Note 6) †. Thus, remarkably, there have been no direct measurements of the kinetic parameters and energy barriers specifically for the ion-transfer step, i.e.…”
Section: Introductionmentioning
confidence: 99%